Co‐Prescription of Strong CYP1A2 Inhibitors and the Risk of Tizanidine‐Associated Hypotension: A Retrospective Cohort Study. Issue 3 (18th October 2018) - Chaugai, Sandip; Dickson, Alyson L.; Shuey, Megan M.; Feng, QiPing; Barker, Katherine A.; Wei, Wei‐Qi; Luther, James M.; Stein, C. Michael; Chung, Cecilia P.
Abstract : Tizanidine, a widely used muscle relaxant that can lower blood pressure, is metabolized by the cytochrome P450 1A2 (CYP1A2). We studied 1, 626 patients prescribed tizanidine and 5, 012 prescribed cyclobenzaprine concurrently with a strong CYP1A2 inhibitor. The primary outcome was severe hypotension, defined as systolic blood pressure (SBP) ≤ 70 mmHg during periods of drug co‐exposure. Severe hypotension occurred more often in the tizanidine group (2.03%; n  =   33) than the cyclobenzaprine group (1.28%; n  =   64); odds ratio (OR) = 1.60; P  =   0.029. This difference remained statistically significant after adjustment for a log‐transformed propensity score that included age, sex, race, Charlson's comorbidity index, and concurrent use of antihypertensive medications (OR = 1.57; P  =   0.049). A sensitivity analysis that defined hypotension as SBP < 90 mmHg also yielded higher rates of hypotension among patients prescribed tizanidine. In conclusion, CYP1A2 inhibition increases the risk of hypotensive episodes associated with the use of tizanidine in routine clinical practice.